Fair play : diversity and conflicts in early Christianity : essays in honour of Heikki Räisänen - Räisänen, Heikki.; Dunderberg, Ismo.; Tuckett, C. M.; Syreeni, Kari. (Novum Testamentum, Supplements, 2002)
This collection of essays in honour of Heikki Räisänen, New Testament professor at the University of Helsinki, consists of 22 essays written by his colleagues and students on Jesus, the gospels, Paul, early Christianity, and biblical interpretation. Räisänen's own research has been characterized by methodological awareness combined with a keen interest in ethical issues. Both these aspects come to expression in his insistence on \'fair play\' as a correct scholarly attitude involving an honest dialogue, a real encounter, and a recognition of diverging opinions. In this spirit, most of the essays in this book lay emphasis on issues related to early Christian diversity and conflicts, and to their challenge in modern society. The book is useful for scholars, academic teachers and students interested in various aspects of the New Testament, early Christianity, and hermeneutics.